The Influence of Work Experience, Competence, and Work Discipline on Teacher Performance with Work Motivation as an Intervening Variable at Nur Al Hiraa Character School - Natasha Eka Murti; Titing Widyastuti; Yoyo Indah Gunawan (Publikasi Indonesia, 2024)
The purpose of this study is to determine the influence of variables such as work experience, competence, and work discipline on teacher performance with work motivation as an intervening variable at Nur Al Hiraa Character School. The type of research used in this study is explanatory type causal research which examines the influence of independent variables on dependent variables. The results of this study show that work experience, competence, work discipline, and work motivation have a significant influence on teacher performance in the f test (simultaneous). It can be concluded that the higher the level of work experience, competence, work discipline, and motivation, the higher the level of teacher performance felt by each teacher.